KONTRIBUSI GAYA BELAJAR PADA AKTIVITAS BELAJAR MATEMATIKA EKONOMI - Rendika Vhalery; Darwin Hartono; Ari Wahyu Leksono (Jurnal Pendidikan Ekonomi, 2019)
Learning activities are consisted of two types which are active learning activities and passive learning activities. Learning activities are assumed has a connection with learning style. It is known on a condition when students learn economy mathematic with their own characteristic. Furthermore, the aim of this research is to know an impact or influence of visual style, auditory, kinesthetic, and read style of learning toward economy mathematic learning activity. This research involves 167 students. The result of this research shows visual learning style and auditory learning style are not give any influence to the economy mathematic learning activity, meanwhile kinesthetic and read learning style give an impact or influence toward the economy mathematic learning activity. Simultaneously, visual learning, auditory learning, kinesthetic learning, and read learning style have a significant influence toward economy mathematic learning activity. The result of this research can be a reference for the further research. DOI: https://dx.doi.org/10.17977/UM014v12i22019p78